Use and transposition of newscasts in the context of teaching-learning of the civil military dictatorship in Chile - Mansilla, Daniela; Jiménez, María Soledad; Piñeiro, Sandra (Revista General de Información y Documentación, 2022)
This article explores the transposition of television newscasts, press releases, and fragments of bibliographical texts from the period of the Chilean civil-military dictatorship (1973-1990), how these documents are used and appropriated in a pedagogical context, and what openings and limitations arise from the modalities in which they are incorporated into the teaching-learning processes. The methodology considered an ethnographic observation of a didactic sequence developed in the subject of History, Geography, and Social Sciences of a third-year-high school course. On the other hand, interviews were conducted with the teacher at different times during the implementation of the unit. In the analysis were considered the documentary composition that was carried out by the teacher through the positioning of the audiovisual document, the pedagogical design guided by slogans, and the relationship that the students established with the documents in a moment of encounter and subsequent development of guided activities and appropriation of the information reflected fundamentally in the writing and class dialogues. Through the study of this case, it is invited to reflect on the opportunity to create spaces for challenging teaching-learning that seeks to rethink the role of the conflict of controversial issues in the construction of a more democratic society and critical citizenship. In addition, regarding how the use and appropriation of documents invites all actors and actresses to become an active part of the pedagogical context that articulates different biographical, institutional, contextual, social, cultural and political tensions, opening spaces for critical thinking, various explanations and multiple voices about/of the recent past.
Keywords: Archive; Human Rights; Controversy; Pedagogy of Memory; Teaching Learning; Use of information; Press; Dictatorship